Overweight and Obesity as Risk Factors of Breast Cancer in Premenopausal and Postmenopausal Women: Meta-Analysis - Fadhila, Shofia Nur; Murti, Bhisma; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2021)
Background: A woman has an increased risk of breast cancer due to increased exposure to the hormone estrogen during her life due to early menarche, late menopause, and/or the absence of childbearing. Epidemiological data show that menopausal status has a risk factor for breast cancer. The aim of this study was to investigate overweight and obesity as risk factors for premenopausal and postmenopausal breast cancer. Subjects and Method: A systematic review and meta-analysis study was conducted by systematically reviewing articles published from 2010-2021 in the PubMed, Google Scholar, SpringerLink and Science Direct databases with the keywords overweight AND obesity AND "breast cancer" OR "breast carcinoma" AND "premenopausal women", overweight AND obesity AND "breast cancer" OR "breast carcinoma" AND "postmenopausal women". Inclusion criteria included articles in English, full text, using an observational study design, and displaying adjusted odds ratios. Articles were reviewed using PRISMA diagrams and analyzed using Revman 5.3. Results: A meta-analysis of 10 articles concluded that overweight women were 1.35 times more likely to develop premenopausal breast cancer than women with a normal BMI (aOR= 1.35; 95% CI= 0.98 to 1.86; p= 0.070). A meta-analysis of 10 articles concluded that obese women were 1.27 times more likely to develop premenopausal breast cancer than women with normal BMI (aOR= 1.27; 95% CI= 0.95 to 1.69; p= 0.110). A meta-analysis of 9 articles concluded that overweight women had a 1.28 times risk of developing postmenopausal breast cancer compared with women with a normal BMI (aOR= 1.28; 95% CI= 1.00 to 1.63; p= 0.050). A meta-analysis of 11 articles concluded that obese women were 1.52 times more likely to develop postmenopausal breast cancer than women with normal BMI (aOR= 1.52; 95% CI= 1.17 to 1.98; p= 0.002). Conclusion: Overweight and obesity increase the risk of pre-menopausal and postmenopausal breast cancer.